Program Classification for Performance-Based Budgeting : How to Structure Budgets to Enable the Use of Evidence - Robinson, Marc (World Bank, Washington, DC, 2015)
This guide provides practical guidance on program classification, that is, on how to define programs and their constituent elements under a program budgeting system. Program budgeting is the most widespread form of performance budgeting as applied to the government budget as a whole. The defining characteristics of program budgeting are: (1) funds are allocated in the budget to results-based programs. For example, the education ministry s budget provides allocations of funds to a primary education program, a secondary education program, and a tertiary education program, while the environment ministry's budget includes a nature conservation program and an anti-pollution program. (2) Line item controls limits imposed by the parliament or the ministry of finance on the amounts ministries can spend on specific types of inputs (such as office supplies, travel, and utilities) are radically reduced, although certainly not entirely eliminated. (3) Good performance information on programs is collected and used in the budget preparation process to assist budget decision makers to determine how much money is allocated to each program. The core objective of program budgeting is improved expenditure prioritization. This guide commences by outlining the basic principle of results-based program classification. It then explains the accounting and organizational structure realities that must also be considered in developing a sound program classification. In the subsequent sections, the guide then discusses sequentially the key specific issues that arise in developing a program classification.